Police and the law - Siti Zaharah Jamaluddin; Norchaya Talib; Zulazhar Tahir (University of Malaya Press, 2015)
The collection of chapters in this book is intended to provide an introduction to the Royal Malaysian Police and highlight specific police powers as provided by the Federal Constitution, Police Act 1967 and the Criminal Procedure Code. The chapters touch on the establishment of the Royal Malaysian Police; its powers of arrest and investigation; the rights of the arrested person and the treatment while in police custody; disciplinary proceedings and civil actions against the police force.